POLITICAL SOCIALIZATION AS A SOCIO-PSYCHOLOGICAL CATEGORY (World Bulletin of Social Sciences, 2023)
The processes of socio-political adaptation of the individual, his perception, development, and integration into the system of political norms, values, knowledge, and development as a member of a particular society and a citizen of the state are in the focus of modern political science and practice. Such interest is quite understandable. Any socio-political problem is to some extent connected with the issues of political socialization of the individual since the political existence of society is largely a manifestation of the diversity of qualities and creative activity of the people who make it up. The reproduction and development of the political structures of any society (without which its sustainable, stable functioning is unthinkable), as well as the socio-political relations inherent in it, the trends and dynamics of their further development, is at the same time the reproduction of the specific qualities and characteristics of the subjects of these relations - members societies that throughout their lives form, maintain and implement these socio-political relations.